CONSTRUCTION OF KUNTOWIJOYO'S THOUGHTS IN ISLAMIC SCIENCE METHODOLOGY AND ITS IMPLICATIONS FOR INDONESIAN ISLAMIC HIGHER EDUCATION - Suliwati, Suliwati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Muslim scholars are trying to ground science in an Islamic perspective. Kuntowijoyo is one of the figures who initiated the concept of Islamic scholarship who seeks to realize Islam as rahmatan lil alamin in his theory. The purpose of this study is to analyze the concept of Kuntowijoyo's thoughts and construct it in Islamic higher education in Indonesia. This research is a type of qualitative research with a library research approach that has two sources of data, namely primary and secondary. The primary source is a rich book of Kuntowijoyo's thoughts and the secondary source is other supporting books and several reputable journals.The results of this study discuss the concept of spiritual maturity which is the basis of the integration system of Islamic education which leads individuals to integrate knowledge based on the elements of monotheism and ethical values so that science and Islam can achieve the final goal, namely Islam as rahmatan lil alamin and the Muslim community as the central actor in knowledge, moderation of Islam as a means of educational construction which contains a new view in realizing a holistic education covering all aspects of science with the values of Islamic teachings as the main source through integralist concepts and scientific objectivity, as for prophetic intellectuality and Islamic higher education scientific buildings as the implications of education which is the mandate of every Muslim in realizing Allah's revelations to other Muslims to call for the truth, fighting evil and always advising each other in matters of faith in Allah swt. The scientific building of Islamic higher education involves UIN Syarif Hidayatullah Jakarta, UIN Maliki Malang, and UIN Sunan Kalijaga Yogyakarta which applies a scientific integration pattern that combines general science and religion with different curriculum concepts but has the same goal.